PENGARUH KEPEMIMPINAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN PADA SYAKILA BAKERY BENGKULU - Novia Novia; M. Galy Njoman Ari Pribowo (UM. Bengkulu, 2023)
This study aims to determine the influence of leadership and employee loyalty at Syakila Bakery Bengkulu, either partially or simultaneously. There are several independent variables (x) which will be discussed in this study, including Leadership and Loyalty which are the object of this study are Employees at Syakila Bakery Bengkulu, totaling 56 people. In this study, several data analysis techniques were used, including using test instruments, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, coefficient of determination, and also hypothesis testing. From the results of the study it was stated that the Leadership Variable was tsig 0.00C> 0.05, so Ha was accepted and Ho was rejected, meaning that Leadership had a significant influence on Employee Performance at the Syakila Bakery Bengkulu employees. The results of further research state that the Loyalty Variable (X2) is equal to 0.001 > 0.05 then Ha is accepted and Ho is rejected, which means that Loyalty has a significant influence on Employee Performance at Syaila Bakery Bengkulu employees. From the results of the study it was stated that the Leadership and Loyalty Variables, which were equal to 0.000 > 0.05, then Ha was accepted and Ho was rejected, that each variable had a significant influence on Employee Performance at Syakila Bakery Bengkulu employees. Keywords: Leadership, Loyalty, Employee Performance